PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR PERBANKAN DI LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2018 - Dede Suharna; Khoirunnisa Thiara (Universitas La Tansa Mashiro, 2020)
This study aims to determine the effect of Intellectual Capital (VACA), (VAHU), (STVA) on Financial Performance (ROA) and (ROE) in Banking Sector Companies in LQ-45 Listed on the Indonesia Stock Exchange (IDX) for the 2012-2018 Period . The method used is a quantitative method, samples taken using the saturated sample method of 5 banking sector companies in LQ-45 listed on the Indonesia Stock Exchange in the period 2012-2018. Testing statistics using the SPSS V.20 application program.The partial test shows that VACA has no effect on (ROA) with a tcount <ttable (1.028 <2.042) with a significant value ≤ 0.05. VACA on ROE has no effect. While VAHU and STVA significantly influence ROA with tcount> ttable (2,943> 2,042) for VAHU value and (2,543> 2,042) for STVA value. Whereas VAHU and STVA have absolutely no effect on ROE.It can be concluded that VACA has no effect on ROA, while VAHU and STVA partially significantly influence ROA. While neither VACA, VAHU and STVA have no effect on ROE in the banking sector companies in LQ-45 which are listed on the Indonesia Stock Exchange (BEI) for the 2012-2018 period.